PRIORITIES AND MAIN TOOLS FOR THE DEVELOPMENT OF THE DIGITAL ECONOMY OF RUSSIA - M. Ya. Veselovsky; M. A. Izmailova; M. S. Abrashkin (Модернизация, инновация, развитие)
Purpose: the purpose of the article is to identify the main tools for the development of the digital economy of Russia. The article explores the priorities and the main tools for the development of Russia's digital economy, as well as problems that hamper the acceleration of these processes. Approaches to the definition of a digitization index, as well as regulatory and legal aspects of the regulation of the digital economy, are considered. The substantiation of the account of foreign experience in the decision of the revealed problems is given. "Digital privatization', "digital leap", "self-digitalization"and "digital reinvestment".Methods: during the research, the main sources of the initial data were the data of consulting agencies, foreign static bureaus, fundamental and applied works of authoritative scientists in the field of digital economy. The research is based on theoretical methods of scientific knowledge, in particular, the use of methods of synthesis and deduction, as well as methods of empirical cognition, which have revealed many problems of the development of the digital economy and the tools that help to solve them.Results: an analysis of the challenges of the economic and technological order in Russia has been carried out and the role of digitalization in these processes has been revealed. Based on a comparison of the indicators of the new technological revolution of Russia with the countries leaders in this field, it was revealed that the share of the digital economy in Russia today is about 4% in the country's GDP, and in the future up to 10% of GDP growth in Russia and for this it is necessary that the Government of the Russian Federation continued the development of digital services, co-financing of promising projects and increasing digital literacy of the population. Instruments for the development of Russia's digital economy, such as digital privatization, digital leap, self-digitalization, and digital reinvestment, were proposed.Conclusions and Relevance: the tools proposed in this study for the development of the digital economy make it possible to intensify the processes of building up the economic potential for a technological breakthrough. Subsequently, they will be transformed into a set of recommendations for practice and government authorities and allow them to change some laws in the field of high technology and innovation support, as well as to adjust the directions of strategic development of economic institutions and forecast models of economic development.